Draft Annual Plan 1988-89 Volume II Part (A) Government of Arunachal Pradesh - Planning Commission (Planning Commission, 1988)
Unfortunately this long felt need could not be fulfilled earlier because of the ban on the creation of posts. Ban has since been lifted. Further it has been approved in principle to create a Directorate of Horticulture. For financing the additional staff requirement and providing with official and residential building, a provision of Rs.147 lakhs is being proposed in the plan. The capital content of the above would be confined to Rs. 97 lakhs.
Government of Arunachal Pradesh, Planning and Development Department